29th Congress of the Italian Society of Neonatology - Lombardy section | Bergamo, 29-30 January 2016 - Luciano Musi; Alessandro Frigiola; Marcello Giovannini; Luca Rosti (La Pediatria Medica e Chirurgica, 2016)
This abstract book contains the abstracts presented at the 29th Congress of the Italian Society of Neonatology - Lombardy section | Bergamo, 29-30 January 2016.